Corporate restructuring and corporate auctions - Audra L. Boone; J. Harold Mulherin (Claremont McKenna College, Department of Economics, 2002)
We study 298 firms that announce the intent to consider restructuring during the 1989 to 1998 period. We find that the actions taken subsequent to the initial restructuring consideration are equally divided between (i) being acquired, (ii) divesting one or more subsidiaries, or (iii) either terminating the process or declaring bankruptcy. There is a greater completion rate in the second half of the sample, which suggests that economywide factors influence the restructuring decision. For the average firm in the sample, restructuring is a positive net present value decision, although sustained positive shareholder returns accrue only to the firms that actually complete restructuring. For a sub-sample of firms that are acquired, we detail the private auction process that is initiated and conducted by the selling firms and their investment banks. In the private auction, 80 percent of the selling firms have multiple bidders, even though only 20 percent of these cases have more than one publicly announced bidder. The depth of the private auction affects the runup of stock prices prior to the formal acquisition offer, suggesting a reinterpretation of the traditional explanations for the variation in premiums across target firms. The use of private auctions by selling firms also suggests one reason for the absence of toeholds in many mergers as well as the occurrence of multiple public bids even when there is only a single public bidder in a merger.
Keywords: 330; Reorganisation; Auktion; Übernahme; Unternehmensentflechtung; Konkurs; Ankündigungseffekt; USA